Evolution, framework, and comparison between Chinese and foreign countries on tourism utilisation of intangible cultural heritage resources based on scientific knowledge map / Bowen Zhang, Shahnaz Mohd Baldev Shah and Marlenny Deenerwan - -, Bowen Zhang; Mohd Baldev Shah, Shahnaz; Deenerwan, Marlenny (UiTM Press, 2024)
This study screened 2,605 relevant core articles from 2000-2023 from the WOS and CNKI databases. With the help of CiteSpace software, a visual analysis tool, the evolution path and development trend of tourism utilisation research on intangible cultural heritage resources in China and foreign countries were analysed. Citespace was chosen to analyse research on tourism use of ICH resources, mainly based on its power and visualisation advantages in bibliometric analysis. The study found that the process of relevant research in China and foreign countries is different, with foreign research starting earlier than that in China. However, Chinese research is progressing rapidly, with a fast but unstable growth rate in the number of articles published. Secondly, the spatial distribution, creative design, and aesthetic judgment of intangible cultural heritage tourism will likely become the direction of future research. Finally, research on the originality of intangible cultural heritage resources utilised in tourism, stakeholder research, and research on the creative development of tourism products are the hotspots of domestic and international academics' attention. This study systematically summarises the research on the tourism utilisation of intangible cultural heritage resources in different cultural contexts. It puts forward relevant suggestions for the future development of tourism utilisation of intangible cultural heritage resources in China and abroad.